Product design: Incorporating make-or-buy analysis and supplier selection. (20th July 2019) - Zhang, Xiang; Zhang, Lei; Fung, Ka Yip; Ng, Ka Ming
Highlights: New product design framework with make-or-buy analysis and supplier selection. Product ingredients are classified and potential ingredient candidates are generated. Product formula, pricing, make-or-buy decisions, and ingredient suppliers are optimized for profits. Two case studies: light duty liquid detergent and controlled release granule herbicide. Abstract: A new product design framework is presented with the simultaneous consideration of make-or-buy analysis and supplier selection. Consumer preferences are first identified. Product ingredients are classified into different types based on their functionalities. For each ingredient type, potential ingredient candidates are generated from material databases or predictions using computer-aided tools. Heuristics and models (e.g., statistical, empirical, and mechanistic) are used to screen the ingredients and to design a process to manufacture a product with the desired product quality. Then, product price and market demand are determined by using a pricing model. After this, make-or-buy decisions are made through heuristics and suppliers are selected to maximize the profit. Two case studies consisting of light duty liquid detergent and controlled release granular herbicide are provided to illustrate the framework.